ANALISIS KUALITAS PELAYANAN JASA PADA PT. BANK BNI SYARIAH - Rosmalinda, Upia (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2016)
In banking business, role of client of vital importance as determinant [of] the way economics. As very institute base on belief socialize this is bank claimed to give optimal service always major quality of service so that the client will lick lips and peaceful in [doing/conducting] transaction [in] banking world. This research is in PT. Bank BNI [of] Moslem law Branch   as a mean to know whether/what service quality with his dimension that is reliability, responsiveness, assurance, empathy and tangible have been applied better by Bank BNI of Moslem law so that can be felt by all client. Data source used by is data or primary data obtained is direct the than data sekunder data or and research object obtained from PT. Bank BNI of Moslem Law. Data collecting use kuesioner and interview. Population in this research is entire/all client of a number of 30.711 client in recent year the data collecting that is year 2014, by sampel as much 100 responder. Writer use quantitative descriptive analysis method From result of research done to be obtained by a result indicating that quality of service with dimension reliability, responsiveness, assurance, empathy and tangible have included in . good category, just only there be still which must be paid attention to and improved again